Intraoperative coagulopathy during cesarean section as an unsuspected initial presentation of COVID-19: a case report - Kelly Elizabeth Kinsey; Eric Ganz; Susan Khalil; Lois Brustman (BMC, 2020)
Abstract Background The world's understanding of COVID-19 continues to evolve as the scientific community discovers unique presentations of this disease. This case report depicts an unexpected intraoperative coagulopathy during a cesarean section in an otherwise asymptomatic patient who was later found to have COVID-19. This case suggests that there may be a higher risk for intrapartum bleeding in the pregnant, largely asymptomatic COVID-positive patient with more abnormal COVID laboratory values. Case The case patient displayed D-Dimer elevations beyond what is typically observed among this hospital's COVID-positive peripartum population and displayed significantly more oozing than expected intraoperatively, despite normal prothrombin time, international normalized ratio, fibrinogen, and platelets. Conclusion There is little published evidence on the association between D-Dimer and coagulopathy among the pregnant population infected with SARS-CoV-2. This case report contributes to the growing body of evidence on the effects of COVID-19 in pregnancy. A clinical picture concerning for intraoperative coagulopathy may be associated with SARS-CoV-2 infection during cesarean sections, and abnormal COVID laboratory tests, particularly D-Dimer, may help identify the patients in which this presentation occurs.